Customer relationship management in the digital age - Shainesh, G.; Sheth, Jagdish N.; Jain, Varsha (Routledge, 2025)
"Customer Relationship Management in the Digital Age charts the concepts, strategies, benefits, and technologies of CRM in an evolving and increasingly digital business landscape. It empowers readers with the skills to use CRM to forge enduring customer connections, optimize experiences, and drive loyalty across diverse industries and markets. Building upon existing literature, this guide offers a holistic approach that bridges theory and practice, making complex CRM concepts accessible to a wide audience. It integrates the latest technological advances, market trends, and customer centric initiatives, providing a comprehensive view of CRM's role in an increasingly customer-driven era. Pedagogical features include case studies, practical strategies and real-world examples, as well as chapter summaries and discussion questions to guide the reader through the key learning points of each chapter. This helpful book enables readers to navigate the complexities of CRM implementation and customer-centric approaches and tailor strategies for B2B and B2C markets. It is particularly suitable for advanced undergraduate and postgraduate students of CRM, Sales Management, Relationship Marketing and Customer Experience Management, as well as reflective practitioners. Online instructor resources include a course manual, test bank and PowerPoint slides"--